Rethinking the Museum. What Turns a Museum Visit into a Lasting Experience? - Rollig, Stella (Actual Problems of Theory and History of Art, 2020)
Since March 2018 the Belvedere is presenting its world-famous collection in a completely new display. Visitors can enjoy over eight hundred years of Austrian art history in addition to displays about the history of the palace and museum and rooms devoted to the subject of Austria and its identity. The new presentation integrates historic, modern and contemporary works to spark inspiring dialogues. The Belvedere’s collection encompasses some 15,000 masterpieces from eight centuries of art history. Around 420 of these works can be seen in the redisplay at the Upper Belvedere. This new arrangement and design sheds fresh light on works by world-famous artists including Rueland Frueauf the Elder, Franz Xaver Messerschmidt, Ferdinand Georg Waldmüller, Gustav Klimt, Erika Giovanna Klien, Egon Schiele, Helene Funke, and Oskar Kokoschka. The concept phase faced the challenge of accommodating the needs of both tourists and the local audience.While the first group has a limited amount of time available, the aim is to inspire the second to keep comingback. The museum’s response was to devise a clear structure, understandable connections, and accessible, succinct exhibition texts. The foremost aim of the new presentation is that the visitors take new experiences and knowledge with them from the Belvedere and can then tell others about it. They are the museum’s best ambassadors. The displays on the ground floor shed light on the history of the Belvedere, introduce Prince Eugene, and offer an insight into the museum archives. Accessible and concise wall texts and object descriptions provide information about the art-historical and thematic rooms while a new signage system assists orientation around the museum. Artworks from the Middle Ages to the end of the Second World War are at the heart of the presentation. This chronology is interrupted by a contemporary intervention, the large installation The Family of Austrians (1993/2018) by Christian Philipp Müller. A further four thematic rooms intersperse the chronological journey through the eras. These rooms address questions about Austria, its history, and identity. Carlone Contemporary, a series of interventions, accompanies the redisplay of the collection at the Upper Belvedere. The interventions are shown in the Carlone Hall on the ground floor and make a reference to the mythological frescoes. In six-month rotations, artists present works that engage with the Baroque pictorial program in the frescoed hall.